2013
DOI: 10.1021/cg401375a
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Cocrystallization for Dissolution Rate Optimization of a Poorly Water-Soluble Drug

Abstract: A continuous manufacturing process, hot melt extrusion (HME), was employed for the development of high quality carbamazepine−saccharin (CBZ−SCH) cocrystals. The produced cocrystals were compared with a prototype prepared by a solvent method. It was found that processing parameters such as temperature, screw speed, and screw configuration were the critical processing parameters. In-line near-infrared analysis demonstrated that cocrystallization takes place gradually during the process along the extruder's mixin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 28 publications
1
43
0
Order By: Relevance
“…Therefore, heat-induced cocrystallization might be the dominant mechanism for the successful extrusion of CBZ-SAC cocrystal. It was reported that the conversion to CBZ-SAC cocrystal can be highly improved as extrusion temperature was higher than the eutectic point of physical mixture (Moradiya et al, 2013) or melting point of cocrystal (Daurio et al, 2011). Therefore, we speculated that heating-induced cocrystallization for CBZ-SAC system was based on eutectics/melts-mediated mechanism, rather than amorphousmediated mechanism.…”
Section: Revealing More Details On Cocrystallization Mechanismmentioning
confidence: 91%
See 3 more Smart Citations
“…Therefore, heat-induced cocrystallization might be the dominant mechanism for the successful extrusion of CBZ-SAC cocrystal. It was reported that the conversion to CBZ-SAC cocrystal can be highly improved as extrusion temperature was higher than the eutectic point of physical mixture (Moradiya et al, 2013) or melting point of cocrystal (Daurio et al, 2011). Therefore, we speculated that heating-induced cocrystallization for CBZ-SAC system was based on eutectics/melts-mediated mechanism, rather than amorphousmediated mechanism.…”
Section: Revealing More Details On Cocrystallization Mechanismmentioning
confidence: 91%
“…Guidance to the manufacture of salt/cocrystal by hot melt extrusion HME has been explored as a scalable and solvent-free method to achieve continuous manufacture of cocrystal, such as CBZ-SAC cocrystal (Moradiya et al, 2013), CBZ-trans-cinnamic acid cocrystal (Moradiya et al, 2014) and theophylline-citric acid cocrystal (Daurio et al, 2011). Processing temperature is the most important parameter in the successful extrusion of cocrystal for some temperature-sensitive systems, such as ibuprofen-nicotinamide cocrystal (Dhumal et al, 2010) and nicotinamide-trans cinnamic acid cocrystal (Daurio et al, 2011).…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…The application of in-line NIR spectroscopy to monitor the extrusion process was demonstrated by Fischer et al [19] who successfully determined the content of ethylene vinyl acetate in a polypropylene matrix. Off-line and in-line reflectance NIR has also been used to monitor the formation of car bamazepine-saccharine [20] and carbamazepine-trans-cinnamic acid [21] cocrystals. However, reflectance NIR contains large amount of noise in the spectra when monitoring a transparent formulation.…”
Section: Introductionmentioning
confidence: 99%